2017
DOI: 10.1002/mc.22664
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variation, increased gene expression, and molecular mechanisms of neurofascin in lung cancer

Abstract: Metastasis and cell adhesion are key aspects of cancer progression. Neurofascin (NFASC) is a member of the immunoglobulin superfamily of adhesion molecules and, while studies on NFASC are inadequate, other members have been indicated pivotal roles in cancer progression and metastasis. This study aimed at increasing the knowledge on the involvement of adhesion molecules in lung cancer progression by studying the regulation and role of NFASC in non‐small cell lung cancer (NSCLC). Here, copy number variations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Overexpression of NAFSC could partially counteracted the inhibitory effect of miR-3650 in HCC metastasis and EMT. Actually, Samulin Erdem et al showed that knockdown of NFASC could decrease the migration of non-small cell lung cancer cells, rearrange the actin cytoskeleton and inhibit F-actin networks [27], which was consistent with our current results. This implying that miR-3650 inhibit the migration and EMT abilities of HCC cells at least in part by directly binding and inhibiting NFASC expression (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Overexpression of NAFSC could partially counteracted the inhibitory effect of miR-3650 in HCC metastasis and EMT. Actually, Samulin Erdem et al showed that knockdown of NFASC could decrease the migration of non-small cell lung cancer cells, rearrange the actin cytoskeleton and inhibit F-actin networks [27], which was consistent with our current results. This implying that miR-3650 inhibit the migration and EMT abilities of HCC cells at least in part by directly binding and inhibiting NFASC expression (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Publicly available databases like TCGA, METABRIC, or GEO, which are common in the cancer research community, help better understand tumor heterogeneity, detect biomarker genes, and define hidden molecular mechanisms in multi-omics research (Xia Q. et al, 2019). Moreover, lines of previous evidence indicate notable relationships between CNA and mRNA, such as there is a high association of CNA with the development and progression of cancers by regulating gene expression level (Huang et al, 2017;Samulin Erdem et al, 2017;Zhou et al, 2017;Gut et al, 2018), as well as the similar regulatory associations between MET and mRNA (Herman and Baylin, 2003;Shen and Laird, 2013). Even a poor grasp of the additional biological complexity of breast tumors neglected at the expression level can be revealed at the DNA methylation level, possibly resulting in finer subgroups with clinical meaning (Rønneberg et al, 2011).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It is generally accepted that somatic CNV is highly associated with the development and progression of numerous cancers by impacting gene expression level [919]. Samulin Erdem et al [13] found that Neurofascin (NFASC) gene is significantly amplified and overexpressed in non-small cell lung cancer (NSCLC) patients and the novel role of NFASC is identified in the regulation of cell motility and NSCLC migration. Dong et al [16] analyzed the copy number alterations and differentially transcribed genes in esophageal cancer and observed a noteworthy association between CNV and differential gene expression for FAM60A, TFDP1, CDC25B and MCM2.…”
Section: Introductionmentioning
confidence: 99%